Comprehensive Analysis of Prognostic Alternative Splicing Signatures in Endometrial Cancer - Chen, Peigen; He, Junxian; Ye, Huixia; Jiang, Senwei; Li, Yunhui; Li, Xiaomao; Wan, Jing (Frontiers in Genetics, 2020)
Background: Alternative splicing (AS) is one of the critical post-transcriptional regulatory mechanism of various cancers and also plays a crucial role in the development of cancers included endometrial cancer (EC). Methods: The splicing data and genes expression profiles of EC was obtained from The Cancer Genome Atlas. The corresponding clinical data was extracted from TCGA-CDR. With univariate Cox regression analysis, least absolute shrinkage and selection operator model and multivariate Cox regression analysis, the survival related alternative splicing events were selected. Functional enrichment analysis was also preformed to understand the functions of these AS events. Splicing factor and alternative splicing regulatory network was constructed to understand the correlation between these AS events. Result: In total, 1826 AS events were identified as survival related events. Functional enrichment analysis showed that these AS events were associated with several immune system-related processes. Then the prognostic signatures were developed based on these survival related events and acted as independent prognostic factor for EC. Splicing factor and alternative splicing regulatory network was also constructed to understand the regulatory mechanisms of AS events in EC. Conclusion: This study comprehensively analyses the role of AS events in EC and develop the prognostic AS signatures of EC.